2015
DOI: 10.1152/ajpheart.00614.2014
|View full text |Cite
|
Sign up to set email alerts
|

TASK-1 current is inhibited by phosphorylation during human and canine chronic atrial fibrillation

Abstract: Atrial fibrillation (AF) is a common arrhythmia with significant morbidities and only partially adequate therapeutic options. AF is associated with atrial remodeling processes, including changes in the expression and function of ion channels and signaling pathways. TWIK protein-related acid-sensitive K+ channel (TASK)-1, a two-pore domain K+ channel, has been shown to contribute to action potential repolarization as well as to the maintenance of resting membrane potential in isolated myocytes, and TASK-1 inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Expression of K 2P 3.1 channels and functional I K2P were increased in cAF patients in our cohort, contributing significantly to AF-associated APD shortening [68]. By contrast, others have found reduced I K2P in a cohort of AF patients with mitral valve disease, which could be rescued by exogenous application of phosphatases [69], suggesting that abnormal regulation of K 2P channel phosphorylation may affect I K2P in certain patient populations. However, also for I K2P it is unknown whether this abnormal phosphorylation is due to reduced dephosphorylation and, if so, which phosphatases and anchoring proteins are involved.…”
Section: Altered Regulation Of Cardiac Electrophysiology and Contrmentioning
confidence: 71%
“…Expression of K 2P 3.1 channels and functional I K2P were increased in cAF patients in our cohort, contributing significantly to AF-associated APD shortening [68]. By contrast, others have found reduced I K2P in a cohort of AF patients with mitral valve disease, which could be rescued by exogenous application of phosphatases [69], suggesting that abnormal regulation of K 2P channel phosphorylation may affect I K2P in certain patient populations. However, also for I K2P it is unknown whether this abnormal phosphorylation is due to reduced dephosphorylation and, if so, which phosphatases and anchoring proteins are involved.…”
Section: Altered Regulation Of Cardiac Electrophysiology and Contrmentioning
confidence: 71%
“…Some studies reported increased channel expression in cAF ( Barth et al, 2005 ; Schmidt et al, 2015 , 2017 ), while no change was found by others ( Ellinghaus et al, 2005 ; Gaborit et al, 2005 ). Similarly, functional measurements have shown both increased ( Schmidt et al, 2015 , 2017 ) and diminished ( Harleton et al, 2015 ) I K,2P amplitudes in cAF.…”
Section: Computational Pharmacology In Afmentioning
confidence: 79%
“…6,7 It also shows phosphorylation-dependent inhibition by protein kinase C 7 and inhibition by platelet activating factor. 6,7 It also shows phosphorylation-dependent inhibition by protein kinase C 7 and inhibition by platelet activating factor.…”
Section: And Inmentioning
confidence: 99%
“…1 Channel functionality of K 2p 3.1 can also be modulated by several other factors: inhibition occurs during hypoxia, in response to α adrenergic 4 and endothelin-1 receptor stimulation 5 and in the presence of the endocannabinoid anandamide (or its stable analog methanandamide). 6,7 It also shows phosphorylation-dependent inhibition by protein kinase C 7 and inhibition by platelet activating factor. 8 In contrast, activation of K 2p 3.1 channels occurs in response to the key inhalational anesthetics halothane, sevoflurane, and isoflurane.…”
mentioning
confidence: 99%